PENGARUH GENDER, INDEKS PRESTASI KUMULATIF, PEMBELAJARAN DAN PENDIDIKAN KEUANGAN TERHADAP LITERASI KEUANGAN SYARIAH - Suriani, Suriani; Mardayanti, Ulfa (Ekonomi Islam, 2024)
The Financial Services Authority (OJK) conducted the 2019 National Survey of Financial Literacy and Inclusion (SNLIK), and the results showed that while conventional financial literacy is at 67.1%, Sharia financial literacy among Indonesian students is still significantly lower at 31.5%. This study looked at how undergraduate students at the Faculty of Economics and Business, Universitas Syiah Kuala, in the even semester of the 2022–2023 academic year, perceived their level of Sharia financial literacy about their gender, grade point average (GPA), financial education in postsecondary institutions, and parental financial education. With 97 respondents in total, probability sampling using a straightforward random sample technique was used for primary data. Multiple linear regression analysis results showed that although other variables showed no discernible influence, financial education in higher education had a significant and favorable impact, appearing as the major factor determining Sharia financial literacy. As such, it is advised that teachers incorporate Sharia financial education into their curricula to improve students' comprehension, which may then be reflected in their grade point average. Furthermore, in addition to pupils' learning efforts, parents are encouraged to offer further support in educating their children about Sharia money. Keywords: Sharia Financial Literacy, Gender, Grade Point Average, Financial Learning, Financial Education.